On Ideals Which Have the Weakly Insertion of Factors Property (Journal of Sciences, Islamic Republic of Iran)
A one-sided ideal of a ring has the insertion of factors property (or simply, IFP) if implies r for . We say a one-sided ideal of has the weakly IFP if for each , implies , for some non-negative integer . We give some examples of ideals which have the weakly IFP but have not the IFP. Connections between ideals of which have the IFP and related ideals of some ring extensions are also shown.